Select Page

Introductory Finance

I need help on 10.1 10.2 and 10.3.

Document Preview:

9.1The Constant-Growth-Rate Discounted Dividend Model, as described equation 9.5 on page 247, says that:P0 = D1 / (k – g)A.rearrange the terms to solve for:i. G ii.  D1.As an example, to solve for k, we would do the following:1.  Multiply both sides by (k – g) to get: P0 (k – g) = D12.  Divide both sides by P0 by to get: (k – g) = D1 / P03.  Add g to both sides: k = D1 / P0 + g (8 marks)Given,P0 = D1 / (k – g)(k-g) * P0 = (k-g)* D1 / (k – g)k- g = D1/P0g = k – D1/P0 Given,P0 = D1 / (k – g)(k-g) * P0 = (k-g)* D1 / (k – g)K*P0- g*P0 = D19.2Notation: Let Pn = Price at time nDn = Dividend at time nYn = Earnings in period nr = retention ratio = (Yn– Dn) / Yn = 1 – Dn/ Yn = 1 – dividend payout ratioEn = Equity at the end of year nk = discount rateg = dividend growth rate = r x ROEROE = Yn / En-1 for all n>0.We will further assume that k and ROE are constant, and that r and g are constant after the first dividend is paid. A.Using the Discounted Dividend Model, calculate the price P0 if D1 = 20, k = .15, g = r x ROE = .8 x .15 = .12, and Y1 = 100 per share P0 = D1/(k-g) = 20/(0.15-0.12) = 666.67  B.What, then, will P5 be if:D6 = 20, k = .15, and g = r x ROE = .8 x .15 = .12? P5 = D6/(k-g) = 20/(0.15-0.12) = 666.67 C.If P5 = your result from part B, and assuming no dividends are paid until D6, what would be P0? P1? P2? P0 = P5/(1+k)^5 = 666.67/(1.15)^5 = 331.45P1 = P5/(1+k)^4 = 666.67/(1.15)^4 = 381.17P2 = P5/(1+k)^3 = 666.67/(1.15)^3 = 438.34 D.Again, assuming the facts from part B, what is the relationship between P2 and P1 (i.e., P2/P1)? Explain why this is the result.If we look at the formulae in part c, we can see the below relationship:P2/P1 = (1+k)This is because if no dividends are paid between the two periods, the only factor that remains is the discount factor.  E.If k = ROE, we can show that the price P0 doesn’t depend on r. To see this, let g = r x ROE, and ROE = Yn / En-1, and since r = (Yn – Dn) / Yn , then D1 = (1 – r) x Y1 andP0=D1 / (k – g)P0=[(1 – r) x Y1]…

Introductory Finance